2004
DOI: 10.1021/es049766f
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Responses of Plankton to a Mixture of Four Tetracyclines in Aquatic Microcosms

Abstract: Pharmaceuticals are routinely detected at low concentrations in surface waters, but effects on non-target organisms are not well understood. Microcosms were used to assess ecological responses in freshwater ecosystems to a mixture offourtetracyclines commonly used in veterinary and human medicine. Triplicate microcosms were treated with tetracycline, oxytetracycline, doxycycline, and chlortetracycline, resulting in measured time-weighted average total mixture concentrations of 0, 0.080, 0.218, 0.662, and 2.29 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 44 publications
3
26
0
1
Order By: Relevance
“…Due to the application of animal wastes as plant nutrient sources and soil amendments, TCs can accumulate in soil to the level of mg kg −1 (Hu et al 2008). Frequent application of TCs has raised emerging threat to ecological safety and human health, such as the adverse effects on soil microbial (ThieleBruhn and Beck 2005) and aquatic photosynthetic organisms (Wilson et al 2004), as well as triggering of the dissemination of antibiotic-resistant genes (Knapp et al 2010). All these Responsible editor: Marcus Schulz Electronic supplementary material The online version of this article (doi:10.1007/s11356-015-4839-2) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the application of animal wastes as plant nutrient sources and soil amendments, TCs can accumulate in soil to the level of mg kg −1 (Hu et al 2008). Frequent application of TCs has raised emerging threat to ecological safety and human health, such as the adverse effects on soil microbial (ThieleBruhn and Beck 2005) and aquatic photosynthetic organisms (Wilson et al 2004), as well as triggering of the dissemination of antibiotic-resistant genes (Knapp et al 2010). All these Responsible editor: Marcus Schulz Electronic supplementary material The online version of this article (doi:10.1007/s11356-015-4839-2) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…Data showed that tetracycline was detected at the concentration ranging from 0.09 to 6.0 μg L −1 in samples from treatment plant effluent, surface water, and ground water (Batt et al 2006). To date, ecological risk assessment of tetracycline has been widely conducted in using data from aquatic organisms (Eguchi et al 2004;Ferrari et al 2004;Wilson et al 2004;Sarmah et al 2006;Jiao et al 2008). However, little work has been performed on adverse biological effects of the antibiotics on agricultural crops.…”
Section: Introductionmentioning
confidence: 99%
“…The identification and grouping of species were according to Wilson et al (2004), the total species richness (plus potential species dominances) and abundance was determined for each trophospecies (Yodzis 1988) group and for the entire community (Yodzis 1988). The use of trophospecies in micro/mesocosm studies is supported by the lack of knowledge in distinguishing the relative ecological niche and roles for the vast majority of species within a group (e.g.…”
Section: Biotic and Abiotic Sampling And Measurement Protocolsmentioning
confidence: 99%
“…Hence, an extensive list of different Rotifera species is empty information with low associated cost-efficiency if unable to distinguish and subsequently model the species ecological traits. Therefore, we recorded the species richness within each group and the total abundance within each group, but not the total abundance of each species within each group (Wilson et al 2004).…”
Section: Biotic and Abiotic Sampling And Measurement Protocolsmentioning
confidence: 99%